Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Pada Lansia Di Masa Pandemi COVID-19 Di Desa Bojonglarang Kecamatan Cijati Kabupaten Cianjur: Relationship between Family Support and Anxiety Levels in the Elderly During the COVID-19 Pandemic in Bojonglarang Village, Cijati District, Cianjur Regency in 2021 - Lestari, Yuspia (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: During the COVID-19 pandemic elderly experience anxiety levels due to fear of contracting the coronavirus, one of the factors that make the level of elderly anxiety increase is the absence of family support in the elderly. COVID-19 (Corona Virus Disease 2019) is a new disease caused by a virus from the Corona Virus group or a disease caused by virus infection severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) or often called the Corona Virus. COVID-19 can cause respiratory system disorders, ranging from mild flu-like symptoms to lung infections, such as pneumonia. COVID-19, known as the Novel Corona Virus, first occurred in the city of Wuhan, China in December 2019. The Corona Virus began spreading to other countries in January 2020. Meanwhile, Indonesia itself announced COVID-19 cases in March 2020 The spread of COVID-19 is currently the most critical global health disaster that has infected more than 100 countries and caused 6,400 deaths.1 On January 7, 2021, COVID-19 cases continued to grow by 87,640,097 cases, which was ranked the highest number of COVID-19 cases, namely the United States with 21,857,616 cases. Meanwhile, Indonesia ranks 20th out of 220 countries infected with Covid-19 with a total number of cases of 797,723 cases (2). Methods: The population in this study was 70 with a sample number of 60 taken using purposive sampling. This research is quantitative with the type of design correlation that is research conducted to connect two variables. Results: The results of the statistical test showed that there was a Mutation of the Relationship between Family Support and Anxiety Levels in the Elderly in Bojonglarang Village, Cijati District, Cianjur Regency in 2021 with the results of a statistical test, the p-value = 0,000 which was < 0,05 so that H0 was rejected and Ha was accepted. Discussion: The relationship between family support and the level of anxiety in the elderly during the COVID-19 pandemic in Bojonglarang Village, Cijati District, Cianjur Regency in 2021, so that families can provide maximum support to the elderly during the COVID-19 pandemic.